SCOPING REVIEW: SUPPORTIVE CARE NEEDS IN YOUNG WOMEN WITH BREAST CANCER - Denisa Novianne Berlianti; Witdiawati Witdiawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2026)
The incidence of breast cancer in young women is increasing globally and nationally, as the disease affects individuals under 40. This condition creates complex, multidimensional needs. Despite high prevalence, specific research on supportive care for this age group remains limited. Unidentified needs risk decreasing quality of life and increasing patients' economic burden. This study aims to identify the supportive care needs of young women with breast cancer. A literature search was conducted via PubMed, Scopus, and EBSCO (2020-2025) using keywords “Young Adults,” “Breast Neoplasms,” and “Supportive Care.” Inclusion criteria were limited to full-text articles in English or Indonesian focusing on breast cancer patients under 50. From 807 identified articles, title/abstract screening and full-text eligibility assessment were performed using the PRISMA Flow Diagram 2020, resulting in 5 final articles for review. Data were extracted and analyzed using narrative synthesis. Results showed that unmet supportive care needs include health systems and information, psychological, sexual, and physical and daily activity domains. In conclusion, young women with breast cancer have various crucial supportive care needs requiring further attention in healthcare. Therefore, studies with more representative sample sizes and stronger designs are recommended to formulate targeted interventions.